A comunidade zooplanctônica em um canal de maré no estuário do rio Caeté, Bragança (Pará, Brasil) - PERES, Ariadne da Costa (Universidade Federal do Pará, 2013)
There are few studies mede about zooplankton in estuaries of Bragança region, Pará State. This work was done in a tidal creek, named Furo do Chato, next to Ajuruteua, Bragança's district which is part of Pará State seashore and aimed to study lhe zooplankton qualitative and quantitative composition, as well as lhe sazonal variations and the environmental effect variables of the zooplankton composition. From August/96 to January/97 every three weeks for a period of 24 hours, zooplankton samples were taken every two hours. Furo do Chato is a tida l creek with strong coaste! influence. Hence the great majority of lhe zooplankton categories found are from coaste! water. Besides holoplankton and meroplankton components, lhe zooplankton samples from Furo do Chato has a strong bentonic component. Ten phyla were identified: Protozoa, Mollusca, Chordata, Annelida, Cnidaria, Arthropoda, Urochodata, Chaetognatha, Nematoda e Bryozoa. The Copepoda class had higher representative, even for density, biomass as well as occurrence frequency in the community. The most abundant and frequent Categories (>40%) were Pseudodiaptomus marshi, Acartia lilljeborgi, Acartia tansa, Harpacticoida, Sagitta sp., Oikopleura dioica, Cnidaria, Isopoda, crabs zoeas, shrimps post-larvae and fish larvae. The average densities and biomass were low (1,07 indiv./m³ e 16,43 mg/m³). The zooplankton community is more abundant in the transition months than in the dry period. The highest abundances took place at night and during the spring lides. Tide, salinity and different moon phases did not infiuence in the zooplankton as a whole, but only in some categories isolated.